2014
DOI: 10.1530/joe-14-0401
|View full text |Cite
|
Sign up to set email alerts
|

H4 histamine receptors inhibit steroidogenesis and proliferation in Leydig cells

Abstract: The histamine H4 receptor (HRH4), discovered only 13 years ago, is considered a promising drug target for allergy, inflammation, autoimmune disorders and cancer, as reflected by a steadily growing number of scientific publications and patent applications. Although the presence of HRH4 has been evidenced in the testis, its specific localization or its role has not been established. Herein, we sought to identify the possible involvement of HRH4 in the regulation of Leydig cell function. We first evaluated its ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…HA dual concentration-dependent effect on steroidogenesis has been described in MA-10 LCs and in purified rat LC. HA positively regulates steroidogenesis at low concentrations via HRH2 and negatively at high concentrations via HRH1 and HRH4 (Mondillo et al 2005, Abiuso et al 2014. Similar results were observed in R2C LCs (Abiuso et al 2018).…”
Section: Introductionsupporting
confidence: 74%
“…HA dual concentration-dependent effect on steroidogenesis has been described in MA-10 LCs and in purified rat LC. HA positively regulates steroidogenesis at low concentrations via HRH2 and negatively at high concentrations via HRH1 and HRH4 (Mondillo et al 2005, Abiuso et al 2014. Similar results were observed in R2C LCs (Abiuso et al 2018).…”
Section: Introductionsupporting
confidence: 74%
“…Last but not least, a recent work in Leydig-cell tumors (LCT), which are rare testicular endocrine tumors shows that H4R agonist VUF8430 treatment inhibited steroidogenesis and proliferation in R2C cells and also reduced pro-angiogenic capacity both in vitro and in vivo . Furthermore, H4R immunostaining was weak in LCT but moderate/strong in normal prepubertal testes (Abiuso et al, 2014, 2018).…”
Section: H4r Expression In Melanoma and Other Cancersmentioning
confidence: 96%
“…Investigation of H1‐H4 receptors in human testis is needed to have a better understanding of such cross talk. Abiuso et al reported the expression of the H4 receptor on MA‐10 Leydig tumor cells and that H4 receptor activation inhibits the proliferation of MA‐10 cells . The biologic role of MCs in cryptorchid testes needs to be studied.…”
Section: Discussionmentioning
confidence: 99%